Patrocínio à cultura: do marketing cultural à responsabilidade social - Miszputen, Francis (2014)
This is a study of the corporate sponsorship to cultural projects, which took place in Rio de Janeiro, between 2010 and 2012, based on the research leaded by Instituto Cidade Viva, in collaboration with the Brazilian service for the small companies - Serviço Brasileiro de Apoio às Micro e Pequenas Empresas (SEBRAE). The study intends to identify sponsorship mechanisms of choice by the Brazilian companies, as well as elucidate evaluation, selection and follow up criteria, besides sponsoring continuity. The final chapter brings a proposition for a new work, based on the acquired knowledge, in association with best statistics practices, which will allow the construction of a Profile of the Corporate Cultural Sponsor in Brazil.